Decentralization in Ethiopia--Who Benefits? - Chaurey, Ritam; Mukim, Megha (World Bank, Washington, DC, 2016)
This paper shows that greater autonomy to cities in Ethiopia through a process of city proclamations, led to better economic outcomes at the city level, lowering regional spatial inequalities. In addition, the newly-empowered cities did not seem to misuse their new powers by favoring particular firms over others. We investigate the effect of a nation-wide introduction of VAT in Ethiopia – and show that the intended recipients of the reform, i.e. importing firms performed better (in terms of employment and sales) only after the VAT introduction in decentralized cities with greater autonomy than in non-decentralized cities. This is suggestive evidence that increasing administrative powers (or the mayor’s wedge) played an important role in making Ethiopian cities more competitive, and allowed mayor’s to transmit more efficiently the effect of national-level reforms.